Which Resilience? Thinking Democratic Subjectivity in the Polycrisis - Alice Koubová (Filozofia)
In the context of the current polycrisis, Andreas Reckwitz suggests that instead of emphasizing progress, Western liberal democracies should cultivate resilience. The question is: which resilience? The prevailing theory of democratic resilience focuses on securing the “invariant core” of democratic institutions. This article shows why this approach is insufficient and discusses the advantages of the multisystemic approach. Democracy is here understood as a quality of the lived relational environment and a regime with social and ethical aspirations. Developing resilience in this context means nurturing the sources of democratic subjectivity and consistently opposing the inner and institutional violations in the society. As such resilience has nothing to do with invulnerability or protection against external threats. Instead it supports the resistance against the double binds caused inside democratic regimes by the neoliberal paradigm in the name of cultivating democratic agonism and transformation.